2019
DOI: 10.5539/ibr.v13n1p136
|View full text |Cite
|
Sign up to set email alerts
|

Manager Attitude Impact on the Performance of Employees “A Case of Jordanian Travel and Tourism Institutions”

Abstract: The present study aimed to examine the role of manager attitude (MA) on enhancing employee performance (EP) at the tourism and travel institutions (TTI) in Jordan. The study population consists of 3700 employees at the TTI located in the capital of Jordan (Amman) as most of institutions located their (97%). A randomly sampling technique was employed at the present study. Collected data were analyzed using Statistical Packages for Social Sciences (SPSS) program. The researcher distributed 132 questionnaires, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
1
9
1
4
Order By: Relevance
“…The more the employee gets training, the more efficient their level of performance would be [15]. The results of this study were supported by [14,16,17] which suggests that training has a significant positive effect on the performance of village government officials.…”
Section: E Implementation Of the Financial System Moderates The Effect Of Training On Village Government Apparatus Performancesupporting
confidence: 58%
“…The more the employee gets training, the more efficient their level of performance would be [15]. The results of this study were supported by [14,16,17] which suggests that training has a significant positive effect on the performance of village government officials.…”
Section: E Implementation Of the Financial System Moderates The Effect Of Training On Village Government Apparatus Performancesupporting
confidence: 58%
“…In fact literature discussed that effective training enhances self-confidence and self-reliance (Alfandi, 2016). In line with the highlights from the literature on the influence of entrepreneurial training effectiveness on perceived behavioral control through building self-confidence (Sila, 2014;Alfandi, 2016), and its consequently influence on intention (Ajzen, 1991), empirical evidence confirmed the significant indirect effect of supervisor support on training which serve as a key to training effectiveness was found on transfer training participation through transfer climate (Nijman and Gelissen, 2011). Training was also found to be indirect predictor of turnover intention through job satisfaction (Kolarova, 2010).…”
Section: Entrepreneurial Training Effectivenessmentioning
confidence: 99%
“…MA found to have an effect on EP at Jordanian travel and tourism institutions. Alfandi, (2020) agreed that MA helped employees to become more effective in carrying out of their duties to improve performance through the increasing level of individual competences. The same result confirmed by several previous studies that found that MA will lead to a high level of EP through, trust, confidence to their employee, and unbiased behavior toward their employees (Seamen & Eves, 2005;Khan et al, 2014;Alfandi, 2016a).…”
Section: Resultsmentioning
confidence: 99%
“…Normally, managers have limited time and resources to interaction with the audience similarly (Zhang, Leng, & Xu, 2019), hence, a high level of trust, respect, and compliance with obligations are the main determinants of the changing relationship and the reason to increase their performance (McNeese-Smith, 1997;Seamen & Eves, 2005). The influence of positive or negative MA on their performances has been confirmed in the literature Seamen & Eves, 2005;Khan et al, 2014;Alfandi, 2020;Truckenbrodt, 2000;Pellegrini & Scandura, 2006;Liden & John, 1998;Scandura & Schriesheim, 1994;Liden & Graen, 1980;Klein & Kim, 1998).…”
Section: Manager Attitudementioning
confidence: 91%